2017
DOI: 10.1080/03670244.2017.1406855
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient Intake and Factors Influencing Eating Behaviors in Older Migrant Women Living in the United Kingdom

Abstract: This study examines nutrient intake and factors influencing eating behaviors in a sample of 76 migrant older women (≥ 60 years) living in the UK. Nutrient intake was assessed using a 24-hr recall enhanced by an in-depth probing dietary interview. Median energy intake was significantly lower than the UK RNIs (5,125.4 v. 7,301.1 kJ/d, p < .001). Main nutrients of concern were retinol, vitamin D, magnesium, potassium, copper, selenium, and monounsaturated fatty acids. Semistructured interviews were conducted with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 34 publications
(29 reference statements)
4
11
0
1
Order By: Relevance
“…Given the importance of micronutrients for maintenance of good health, physical function and better quality of life, the low intakes are of concern, particularly when one considers the relatively high prevalence of non-communicable disease within this population [10]. The inadequate intake of various nutrients among older ethnic minorities in the present study is consistent with previous studies in the UK and elsewhere [11,49]. However, in contrast to the present findings, the results from Years 7 and 8 (combined) of the UK NDNS Rolling Programme (a sample comprised of predominately white older adults), found that intakes of most micronutrients were at the RNI or above the RNI [45].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Given the importance of micronutrients for maintenance of good health, physical function and better quality of life, the low intakes are of concern, particularly when one considers the relatively high prevalence of non-communicable disease within this population [10]. The inadequate intake of various nutrients among older ethnic minorities in the present study is consistent with previous studies in the UK and elsewhere [11,49]. However, in contrast to the present findings, the results from Years 7 and 8 (combined) of the UK NDNS Rolling Programme (a sample comprised of predominately white older adults), found that intakes of most micronutrients were at the RNI or above the RNI [45].…”
Section: Discussionsupporting
confidence: 86%
“…For instance, as evident in the findings of the Health Survey England (HSE), the prevalence of obesity among Black African women is 38% (risk ratio 2.0), and 32.1% among Black Caribbean women (risk ratio 1.43) compared to 23% in the general white British population of women [ 10 ]. While recognising these differences in health outcomes, dietary habits of BMEs have been shown to become unhealthy mainly due to financial constraints, language barriers, age, availability of traditional foods, and years spent in the host country [ 11 13 ]. A study in the UK found that older BME women with a mean age of 70.5 years had inadequate intakes of vitamin D, selenium, magnesium and potassium, and attributed reasons such as age, reduced physical activity and dietary restrictions to be influencing dietary intake [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the importance of micronutrients for maintenance of good health, physical function and better quality of life, the low intakes are of concern, particularly when one considers the relatively high prevalence of noncommunicable disease within this population [10]. The inadequate intake of various nutrients among older ethnic minorities in the present study is consistent with previous studies in the UK and elsewhere [11,48]. However, in contrast to the present ndings, the results from Years 7 and 8 (combined) of the UK NDNS Rolling Programme (a sample comprised of predominately white older adults), found that intakes of most micronutrients were at the RNI or above the RNI [44].…”
Section: Discussionsupporting
confidence: 86%
“…The strengths of this study include the use of the multiple-pass 24-hour recall approach on four-non-consecutive days (including a weekend day) compared to the use of a single 24-hour recall by previous studies which fails to account for day-to-day variation, or the FFQ which has been found to overestimate energy and nutrient intakes in older adults [11,27,66]. However, it is important to acknowledge the high possibility of under-reporting and recall bias in this study.…”
Section: Discussionmentioning
confidence: 99%